Legal Protection for Victims of Illegal Investment through Loss Recovery - Yusuf Wahyu Prayudha (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
The fast expansion of digital asset trading, especially in cryptocurrency, comes with considerable dangers due to unpredictable market fluctuations and uncertain regulations, resulting in a rise in illegal investment scams and substantial losses for the victims. In response to this pressing issue, this research aims to analyze the characteristics of cryptocurrency investment in digital investment and victim fund recovery as legal remedies for consumers in illegal investment. The research approach used includes the statutory approach, conceptual approach, and case study. The research results show that digital investment actors demonstrate significant growth in digital asset trading volumes such as cryptocurrency. However, while the digital investment model provides enormous potential, there are also several risks related to market volatility and regulatory uncertainty. Victim fund recovery as legal remedies for consumers in illegal investment as a form of legal protection for victims of illegal digital investment fraud crimes is a form of protection for society, which can be realized in various forms, such as fulfilling victims' rights namely compensation - something given to parties who experience losses proportional to calculating the losses they experienced.